Youth mobilization and the peace movement: a comparative analysis of resistance struggles in Czechoslovakia, China and Bangladesh - Muhammad Irfan Mahsud; Ayesha Fatima; Zoha Aleem (Department of Government Studies, Universitas Muhammadiyah Makassar, 2026)
The Velvet Revolution in Czechoslovakia, the Tiananmen Square protests in China, and the Quota Movement in Bangladesh are three historically significant nonviolent movements that have had a profound and lasting impact on modern history, each characterized by the active participation of young people. This study aims to compare and contrast the dynamics of these three movements. This study explores secondary sources, including books, newspapers, archives, scholarly research articles, and journal publications, and analyzes them using an explanatory narrative approach. The findings indicate that although all three were driven by collective aspirations for democracy and social reform, the outcomes varied significantly. The similarities and differences lie in factors such as the role of youth leadership, the scale and nature of the youth demonstrators, the influence of social media, government responses, and broader implications. Thus, a key contribution of this study is that it highlights young people as the initiators, organizers, and symbols of resistance. The study seeks to understand the conditions that lead to the success or failure of youth-led nonviolent actions. Although there is a substantial body of literature on this topic, comprehensive comparative analyses of these movements remain scarce, underscoring the importance of this study.